Clarifications of and improvements to the equations used to calculate the levelized cost of electricity (LCOE), and comments on the weighted average cost of capital (WACC). (15th September 2020) - Harvey, L.D. Danny
Abstract: The levelized cost of electricity (LCOE) is a metric commonly used in the academic literature. Electricity-supply projects can be financed by the project developer, equity partners, or through debt, with the timing of investments and returns different for all three. The LCOE metric is equally applicable to all three sources of financing although the calculation does not explicitly represent these differences in timing. The LCOE metric implicitly assumes that surplus revenue earned during the operation of a powerplant can be re-invested with a rate of return equal to the return on equity, an assumption that is not valid. A modified LCOE equation that accounts for this difference and for steadily declining output and increasing O&M costs is presented here. The errors entailed in using a simple weighting of the returns to equity and debt (the weighted average cost of capital, WACC) in the non-linear LCOE equation entails an error of less than 0.5% if the interest rate on surplus revenues equals the discount rate. Otherwise, it is necessary to separately consider the equity and debt financing portions (even if returns to equity and debt are the same, as the modified LCOE equation applies only to the debt portion). Highlights: The LCOE equation is equally applicable to alternative financing structures. A modified LCOE equation accounts for interest rate differing from discount rate. A modified LCOE equation accounts for increasing O&M costs and declining output. Use of WACC should be abandoned in favor of separate debt and equity calculations.